Mycorrhizal spores associated Lysobacter soli and its plant growth promoting activity - Lasudee K. (2017)
© 2017, Chiang Mai University. All rights reserved. In this study, a strain of Lysobacter soli was isolated from spores of arbuscular mycorrhizal fungus, Glomus mosseae and evaluated for its plant growth promoting activities. This strain was able to produce 8.23 ± 0.02 μg ml -1 of indole-3-acetic acid. It also produced 23.86 ± 0.002 and 39.17 ± 0.002 μg L -1 of hydroxamate and catecholate types siderophore, respectively. Phosphate solubilization was visible on Pikovskaya plate with 12.44 ± 0.05 mg L -1 of solubilized P-released in the culture broth. The inoculation of this strain with mung bean seeds resulted in a significant increase in fresh weight, root length and total length. This is the first report on plant growth promoting activity of L. soli associated with spores of G. mosseae.